(untitled) (Research, Society and Development, 2020)
Objective: to detect the occurrence of leprosy in the main cities of Baixada Maranhense, relating to demographic factors and clinical aspects. Method: This is a retrospective, descriptive and analytical study of data contained in the notification / investigation form of the National Notifiable Disease Information System (SINAN) and in the Department of Informatics of the Unified Health System (DATASUS) of new cases of leprosy. Results: The prevalence was higher in males and in the age group above 15 years, with schooling up to elementary school and mixed race. Regarding clinical characteristics, the multibacillary operational classification was the most prevalent. The municipality of Pinheiro had the highest number of prevalent cases in the last 5 years, with 198 (46.5%), followed by Viana, with 92 (21.6%). In 2013 there was a prevalence of 78 (18.3%) cases, however in 2014 the highest number of prevalent cases was obtained, with 99 (23.2%), in 2015 there were 90 (21.1% ), in 2016, 93 (21.8%) cases were registered, and in 2017, their lowest prevalence was obtained, with 66 (15.5%) cases per year in the municipalities under study. Conclusion: There is a higher occurrence in the MB operational form in all municipalities in the years 2013 to 2017. The predominant characteristics in the population with leprosy in this study were male, aged over 15 years, low level of education and the form leprosy disease was more prevalent among multibacillary forms. Therefore, measures are needed to facilitate early diagnosis in order to prevent the disease from spreading to more advanced cases and not generating a greater impairment in terms of the degree of disability.